Selecting antagonistic yeast for postharvest biocontrol of Colletotrichum gloeosporioides in papaya fruit and possible mechanisms involved - Hassan, Hamizah; Tengku Muda Mohamed, Mahmud; Yusoff, Siti Fairuz; Mohd Hata, Erneeza; Tajidin, Nor Elliza (MDPI AG, 2021)
Colletotrichum gloeosporioides causes anthracnose disease in papaya fruit resulting in tremendous economic loss due to its latent infection. This study aimed to evaluate the biocontrol activity of antagonistic yeasts against C. gloeosporioides in papaya and determine the possible mechanism involved. One hundred and ten yeast strains were isolated from different parts of the papaya plant. Among them, only five strains, namely F001, F006, L003, FL013 and LP010, showed more than 55% radial growth inhibition of C. gloeosporioides. These five potent yeast strains were further evaluated in vitro and in vivo. The results indicated that strain F001 had the strongest biocontrol activity based on spore germination and fungal growth inhibition. In vivo, the strain F001 caused 66.7% and 25% reductions in disease incidence and severity, respectively. Based on molecular identification, the strain F001 was confirmed as Trichosporon asahii. Despite there was no significant induction of defense enzyme activities found on the treated fruits, SEM observation showed direct attachment of T. asahii with the fungal hyphae and interfere in their establishment to the fruit surface. Based on these findings, the antagonistic yeast T. asahii strain F001 may be used as a potential natural biological control agent against anthracnose disease in papaya fruit.